Long term survival after intensive care. Issue 6761 (17th November 1990) - Ridley, S; Jackson, R; Findlay, J; Wallace, P
Abstract : OBJECTIVE–To examine the long term survival of critically ill patients admitted to an intensive therapy unit and to ascertain the effects of age, severity of illness, and diagnostic category at admission on survival. DESIGN–Retrospective observational study with prospectively gathered data on all patients admitted to the unit between June 1985 and July 1987 and followed up until 1 January 1989. SETTING–Regional intensive therapy unit. PATIENTS–513 critically ill adult patients, 16 of whom were excluded because measurements on severity of illness scoring were not available. MAIN OUTCOME MEASURES–Age, severity of illness (determined with the acute physiology and chronic health evaluation (APACHE) II score), and diagnostic category on admission; deaths in the unit; and long term survival after discharge. Details of the survivors were sent to the Registrar General for Scotland, who issued copies of death certificates for the patients who had died between discharge and 1 January 1989. RESULTS–Of 497 patients, 119 (24%) died in the intensive therapy unit and 120 (24%) after discharge, leaving 258 (52%) who were still alive at two years. The median (APACHE II) score was 13 and about half of the patients were aged 55 years or more. A wide range of critical illnesses, except neurosurgical emergencies, were treated. Survival analysis showed that only 41 (34%) of 122 patients with an APACHE II score of greater than or equal to 20 were alive at one year (95% confidence interval 25 to 42) compared with 124 (80%) of 155 patients with a score of less than 10 (73 to 87). Of the 144 patients aged 65 or more, only 68 (47%) survived to one year (39 to 55) but 90 (83%) of the 109 patients aged between 18 and 34 survived a similar period (76 to 71). Mortality was also related to diagnostic category; 71% of trauma victims survived to one year compared with only 41% of those admitted with gastrointestinal pathology. Univariate analysis of the results showed that age, severity of illness, and diagnosis were all predictors of long term survival. Multivariate analysis, however, showed that only age and severity of illness were independent prognostic factors. CONCLUSIONS–Long term survival of patients treated in an intensive therapy unit is related to severity of illness and to age. The outcome from critical illness in the elderly population is poor.